A review on the factors influencing biohydrogen production from lactate: The key to unlocking enhanced dark fermentative processes. (March 2021) - García-Depraect, Octavio; Castro-Muñoz, Roberto; Muñoz, Raúl; Rene, Eldon R.; León-Becerril, Elizabeth; Valdez-Vazquez, Idania; Kumar, Gopalakrishnan; Reyes-Alvarado, Luis C.; Martínez-Mendoza, Leonardo J.; Carrillo-Reyes, Julián; Buitrón, Germán
Graphical abstract: Highlights: Lactate-based H2 -fermentation systems are extensively reviewed. Substrate features, culture conditions and biological factors are discussed in detail. Lactate-to-H2 route is promising to deal with lactate producers' over-proliferation. The proposed approach can be applied for cheese whey, food waste, vinasse and others. Balanced microbial equilibrium required to maintain acceptable hydrogen productivity. Abstract: Dark fermentation (DF) is one of the most promising biological methods to produce bio-hydrogen and other value added bio-products from carbohydrate-rich wastes and wastewater. However, process instability and low hydrogen production yields and rates have been highlighted as the major bottlenecks preventing further development. Numerous studies have associated such concerns with the inhibitory activity of lactate-producing bacteria (LAB) against hydrogen producers. However, an increasing number of studies have also shown lactate-based metabolic pathways as the prevailing platform for hydrogen production. This opens a vast potential to develop new strategies to deal with the "Achilles heel" of DF – LAB overgrowth – while untapping high-performance DF. This review discusses the key factors influencing the lactate-driven hydrogen production, paying particular attention to substrate composition, the operating conditions, as well as the microbiota involved in the process and its potential functionality and related biochemical routes. The current limitations and future perspectives in the field are also presented.